The Role of MRI in Modern Radiology: Enhancing Diagnostic Accuracy Across Specialties - Talal Ali Almalki; Sameeh Saleem Alharbi; Ahmad Berki Alsulami; Mohammed Salamah Alhazmi; Owaydhah Bakheet Aldosari; Saleh Ahmad Naseef; Ahmed Hamood Al Saadi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The field of magnetic resonance imaging (MRI) has advanced dramatically, improving diagnostic precision in several medical disciplines. This development is ascribed to advances in imaging methods, which have made MRI an essential non-invasive diagnostic tool. The main facets of MRI’s function in contemporary radiology are described in the sections that follow. AI has the potential to completely transform radiology, all things considered. AI has the potential to greatly raise the standard and effectiveness of radiology procedures by automating difficult tasks, improving diagnostic capabilities, and streamlining workflows. Unlocking AI’s full potential and overcoming the obstacles that come with its adoption will require ongoing research, development, and cooperation. Applications of artificial intelligence (AI) in radiology Numerous subfields have seen improvements in diagnostic capabilities as a result of AI’s revolutionary contributions to radiology. Better patient outcomes result from radiologists using these AI-driven technologies to interpret medical images more accurately, quickly, and consistently. The specific uses of AI in different radiology subfields are listed below.Furthermore, by enabling more focused treatment strategies, MRI’s ongoing development has wider ramifications for developing personalized medicine and enhancing patient outcomes in general. As the field develops, there is a need for continued innovation and work to make MRI technology more accessible to all patients